A method of conserving ancient iron artefacts retrieved from shipwrecks using a combination of silane self-assembled monolayers and wax coating. (15th July 2017) - Ashkenazi, D.; Nusbaum, I.; Shacham-Diamand, Y.; Cvikel, D.; Kahanov, Y.; Inberg, A.
Highlights: Conservation method is proposes for ancient iron artefacts retrieved from shipwrecks. The proposed treatment is based on a bi-layered coating. The bi-layered coating is made of silane SAM covered by a thicker waxlayer. This coating ensures full coverage of the metal and serves as a corrosion barrier. Abstract: Iron artefacts corrode severely in a marine environment, and require further conservation after retrieval. This research proposes a novel conservation method, based on a bi-layered concept: a thin silane self-assembled monolayer serving as nano-scale barrier, covered by a thicker waxlayer, which is applied by dipping the object into a suitable solution. An accelerated corrosion test was performed, using modern cast iron and steel samples, and repeated on archaeological wrought iron artefacts retrieved from shipwrecks. This protection, which can be easily applied, was found to improve the corrosion resistance of the artefacts.